Gut-derived bacterial flagellin induces beta-cell inflammation and dysfunction. (31st December 2022) - Scheithauer, Torsten P.M.; Herrema, Hilde; Yu, Hongbing; Bakker, Guido J.; Winkelmeijer, Maaike; Soukhatcheva, Galina; Dai, Derek; Ma, Caixia; Havik, Stefan R.; Balvers, Manon; Davids, Mark; Meijnikman, Abraham S.; et al.
ABSTRACT: Hyperglycemia and type 2 diabetes (T2D) are caused by failure of pancreatic beta cells. The role of the gut microbiota in T2D has been studied, but causal links remain enigmatic. Obese individuals with or without T2D were included from two independent Dutch cohorts. Human data were translated in vitro and in vivo by using pancreatic islets from C57BL6/J mice and by injecting flagellin into obese mice. Flagellin is part of the bacterial locomotor appendage flagellum, present in gut bacteria including Enterobacteriaceae, which we show to be more abundant in the gut of individuals with T2D. Subsequently, flagellin induces a pro-inflammatory response in pancreatic islets mediated by the Toll-like receptor (TLR)-5 expressed on resident islet macrophages. This inflammatory response is associated with beta-cell dysfunction, characterized by reduced insulin gene expression, impaired proinsulin processing and stress-induced insulin hypersecretion in vitro and in vivo in mice. We postulate that increased systemically disseminated flagellin in T2D is a contributing factor to beta-cell failure in time and represents a novel therapeutic target.